2020
DOI: 10.1002/aocs.12453
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Deodorization Design for Four Different Kinds of Vegetable Oil in Industrial Trial to Reduce Thermal Deterioration of Product

Abstract: Trans fatty acids (TFA) have been shown to be associated with various health disorders. Due to thermal stress, one major source of dietary TFA is high-temperature deodorization of vegetable oils. In this study, precision minimal deodorization was proposed to obtain healthier "zero-TFA" vegetable oils (TFA ≤0.3%). By optimizing temperatures for different deodorizers, dual columns with dual temperatures (DCDT) deodorizers were proposed, transformed, and industrially implemented among dozens of plants. The deodor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…The optimums of the operating parameters pressure/temperature P/T = 450 kPa/148 °C, processing time t = 30.0 s/cycle, and number of MFA cycles C = 7, were for the optimum reduction ratios (RR) of 91.1, 98.5, 99.3, and 88.2% for E-2-hexenal, heptanal, octanal, and nonanal, respectively. As indicated in research works by [ 27 ] on soybean oil deodorization, MFA technology applied with optimized conditions shows a high efficiency also on crude palm oil as the optimum reduction ratio (RR) of decanal was 81.5% for the pressure/temperature, processing time, and number of cycles optima of 200 kPa/120 °C, 30.0, and 7, respectively. Based on the research work of Liu et al (2021), the results of this study clearly indicate the disadvantage of the high-temperature (240–250 °C) conventional deodorization process during 2–3 h versus the advantage of MFA as an innovative process in the deodorization process without thermal deterioration of the product.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The optimums of the operating parameters pressure/temperature P/T = 450 kPa/148 °C, processing time t = 30.0 s/cycle, and number of MFA cycles C = 7, were for the optimum reduction ratios (RR) of 91.1, 98.5, 99.3, and 88.2% for E-2-hexenal, heptanal, octanal, and nonanal, respectively. As indicated in research works by [ 27 ] on soybean oil deodorization, MFA technology applied with optimized conditions shows a high efficiency also on crude palm oil as the optimum reduction ratio (RR) of decanal was 81.5% for the pressure/temperature, processing time, and number of cycles optima of 200 kPa/120 °C, 30.0, and 7, respectively. Based on the research work of Liu et al (2021), the results of this study clearly indicate the disadvantage of the high-temperature (240–250 °C) conventional deodorization process during 2–3 h versus the advantage of MFA as an innovative process in the deodorization process without thermal deterioration of the product.…”
Section: Resultsmentioning
confidence: 94%
“…As indicated in research works by [27] on soybean oil deodorization, MFA technology applied with optimized conditions shows a high efficiency also on crude palm oil as the optimum reduction ratio (RR) of decanal was 81.5% for the pressure/temperature, processing time, and number of cycles optima of 200 kPa/120 • C, 30.0, and 7, respectively. Based on the research work of Liu et al (2021), the results of this study clearly indicate the disadvantage of the high-temperature (240-250 • C) conventional deodorization process during 2-3 h versus the advantage of MFA as an innovative process in the deodorization process without thermal deterioration of the product. Chromatographic measurements quantified and identified the saturated and unsaturated fatty acids in palm oil treated under various MFA operating parameters.…”
Section: Optimization Of Amf Pretreatmentmentioning
confidence: 88%
“…Therefore, it is necessary to monitor and control the deodorization temperature since trans fatty acid formation reaches a high level at temperatures above 240 °C. [6] There are several reports indicating that trans isomers of fatty acids may cause numerous diseases such as inflammations, cardiovascular diseases, and cancers. [3,4] In conclusion, considering the fatty acid composition of vegetable oils, virgin and cold-pressed ones are better choices due to the unchanged profile of fatty acids and absence of trans isomers in them.…”
Section: Fatty Acidmentioning
confidence: 99%
“…[ 2 ] Although literature has indicated that the refining process does not have an extensive effect on the fatty acid profile of oils, high temperature of deodorization could lead to the formation of trans fatty acids, especially in omega‐3‐rich oils. [ 6 ] Fatty acid composition can be affected by deodorization step during the refining process. Therefore, it is necessary to monitor and control the deodorization temperature since trans fatty acid formation reaches a high level at temperatures above 240 °C.…”
Section: Nutritional Aspectsmentioning
confidence: 99%
“…Estudios previos han aplicado la desodorización en otros productos como aceites B. Abril, 2023 50 vegetales (soja, colza, maíz y girasol) (Liu et al,2021) o de pescado (de Oliveira et al, 2016). También se ha aplicado al pescado y especias (Silva et al, 2005), entre otros alimentos.…”
Section: Desodorización De Alimentosunclassified